MSMEs Competitiveness and Potential Capital Improvement Through Improving The Financial Statement Quality - Yayu Putri Senjani (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
The development of MSMEs started to contribute to the country's economy requires an increase in resources. The resources consist of human resources and assets in the form of funds. There are two options for adding funds, namely through loans and issuing shares. This study aimed to analyze the competitiveness of MSMEs in relation to the Capital Improvement Potential through Quality Improvement of Financial Statements. This research is a quantitative descriptive study. Data is distributed using a questionnaire aimed at Investors with the Convenience Random Sampling method and conducting a related literature review. Simple statistical data processing using Ms. Excel. The results showed that MSMEs have the opportunity to obtain capital from investors. MSMEs capital improvement opportunities can be achieved by improving the quality of financial reporting. Capital obtained from MSMEs can improve the competitiveness of MSMEs